Prevalence of anxiety among gestational diabetes mellitus patients: a systematic review and meta-analysis - Lee, Kai Wei; Loh, Hong Chuan; Chong, Seng Choi; Ching, Siew Mooi; Devaraj, Navin Kumar; Tusimin, Maiza; Abdul Hamid, Habibah; Hoo, Fan Kee (Baishideng Publishing Group Lee KW, Loh HC, Chong SC, Ching SM, Devaraj NK, Tusimin M, Abdul Hamid H, Hoo FK. Prevalence of anxiety among gestational diabetes mellitus patients: A systematic review and meta-analysis. World J Meta-Anal 2020; 8(3): 275-284, 2020)
Background: A diagnosis of gestational diabetes mellitus (GDM) negatively influences maternal mental health. There is a lack of systematic review and meta-analysis on prevalence of anxiety among GDM women. AIM To pool data from existing literature to determine the pooled estimates for the prevalence of anxiety among women diagnosed with GDM. Methods: We searched multiple databases including MEDLINE, Cinahl, PubMed and Scopus to identify studies published up to 31 October 2019 with data on the prevalence of anxiety among women diagnosed with GDM. Data were extracted from published reports. Estimates were pooled using random-effects meta-analyses. Results: We reviewed 19 abstracts, retrieved 10 articles and included three studies incorporating 12744 GDM women from three countries. The pooled prevalence of anxiety was 29.5% (95%CI: 6.9, 52.0) among GDM women. Conclusion: Prevalence of anxiety among GDM women was high. We suggest that epidemiological studies on anxiety should be conducted urgently as it merits clinical attention. In addition, it is important to identify factors associated with anxiety among women diagnosed with GDM.